Clinical signs, MRI findings and long‐term outcomes of foraminal and far lateral thoracolumbar intervertebral disc herniations in dogs. (12th March 2022) - Silva, Sara; Guevar, Julien; José‐López, Roberto; De Decker, Steven; Brocal, Josep; de la Fuente, Cristian; Durand, Alexane; Forterre, Franck; Olby, Natasha; Gutierrez‐Quintana, Rodrigo
Abstract: Background: As they have been seldomly described in the veterinary literature, the aims of this retrospective study were to describe the clinical presentation, MRI findings and long‐term outcome after medical or surgical treatment of dogs presenting with foraminal and far lateral thoracolumbar intervertebral disc herniations. Methods: Retrospective multicentre study of dogs diagnosed with foraminal and far lateral thoracolumbar intervertebral disc herniations between 2009 and 2020 in seven referral hospitals. Results: Thirty‐seven dogs were included. Dachshunds and mixed breeds were most affected. Median age at presentation and duration of clinical signs were 6 years and 14 days, respectively. Pain was the most frequent clinical finding (92%), particularly on spinal palpation and/or hip manipulation, followed by pelvic limb lameness (71%). Eighty‐seven percent of herniations occurred at L5‐L6 or L6‐L7. A good to excellent outcome was seen in 95% of surgically and 90% of medically treated dogs. Conclusion: Although much less frequently recognised than herniation affecting the vertebral canal, foraminal and far lateral thoracolumbar intervertebral disc herniations should be considered in the differential diagnosis list of chondrodystrophic dogs presenting with pain and pelvic limb lameness. Most dogs had a good to excellent outcome following medical or surgical treatment.